Chrysin directing an enhanced solubility through the formation of a supramolecular cyclodextrin–calixarene drug delivery system: a potential strategy in antifibrotic diabetes therapeutics - Hermenean, Anca; Dossi, Eleftheria; Hamilton, Alex; Trotta, Maria Consiglia; Russo, Marina; Lepre, Caterina Claudia; Sajtos, Csilla; Rusznyák, Ágnes; Váradi, Judit; Bácskay, Ildikó; Budai, István; D’Amico, Michele; et al. (MDPI, 2024)
Calixarene 0118 (OTX008) and chrysin (CHR) are promising molecules for the treatment of fibrosis and diabetes complications but require an effective delivery system to overcome their low solubility and bioavailability. Sulfobutylated β-cyclodextrin (SBECD) was evaluated for its ability to increase the solubility of CHR by forming a ternary complex with OTX008. The resulting increase in solubility and the mechanisms of complex formation were identified through phase-solubility studies, while dynamic light-scattering assessed the molecular associations within the CHR-OTX008-SBECD system. Nuclear magnetic resonance, differential scanning calorimetry, and computational studies elucidated the interactions at the molecular level, and cellular assays confirmed the system’s biocompatibility. Combining SBECD with OTX008 enhances CHR solubility more than using SBECD alone by forming water-soluble molecular associates in a ternary complex. This aids in the solubilization and delivery of CHR and OTX008. Structural investigations revealed non-covalent interactions essential to complex formation, which showed no cytotoxicity in hyperglycemic in vitro conditions. A new ternary complex has been formulated to deliver promising antifibrotic agents for diabetic complications, featuring OTX008 as a key structural and pharmacological component.
Keywords: OTX008; chrysin; sulfobutylated β-cyclodextrin; ternary complex; solubilization mechanism; molecular simulation; fibrosis